Geochronology, petrogenesis and tectonic implications of the Zhongchuan granitic pluton in the Western Qinling metallogenic belt, China. (5th July 2012) - Zhu, Laimin; Zhang, Guowei; Yang, Tao; Wang, Fei; Gong, Hujun
<x xml:space="preserve">Abstract</x> The Zhongchuan district is an important component of the metallogenic belt in the Western Qinling. The Zhongchuan granite pluton occurring in the centre of the Zhongchuan metallogenic area has been poorly constrained, though the Triassic granite in Western Qinling has been well documented. In‐situ zircon U–Pb ages, Hf isotopic compositions and whole‐rock geochemical data are presented for host granite and mafic microgranular enclaves (MMES) from the Zhongchuan pluton, in order to constrain its sources, petrogenesis and tectonic setting of the pluton. The distribution of major, trace and rare earth elements apparently reflect exchange between the MMES and the host granitic rocks mainly due to interactions between coeval felsic host magma and mafic magma. The zircon U–Pb age of host granite (231.6 ± 1.5 to 235.8 ± 2.3 Ma) has overlapping uncertainty with that of the MMES (236.6 ± 1.3 Ma), establishing that the mafic and felsic magmas were coeval. The Hf isotopic composition of the MMES (εHf(t) = −13.4 to 4.0) is distinct from the host granite (εHf(t) = −15.7 to 0.0), indicating that both enriched subcontinental lithosphere mantle (SCLM) and crustal sources contributed to their origin. The zircons have two‐stage Hf model ages of 1064 to 1798 Ma for the host granite and 858 to 1747 Ma for the MMES. This suggests that the granitic pluton was likely derived from partial melting of a Late Mesoproterozoic crust, with subsequent interaction with the SCLM‐derived mafic magmas in tectonic affinity to the South China Block. Copyright © 2012 John Wiley & Sons, Ltd.